2013
DOI: 10.4103/0970-9290.116699
|View full text |Cite
|
Sign up to set email alerts
|

Assesment of artificial caries lesions through scanning electron microscopy and cross-sectional microhardness test

Abstract: This methodology can be used to induce AAWSLs in human dental enamel but surface erosion has to be taken into account when performing CSMH test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In initial carious lesions, the relatively intact surface layer generally exhibits a clearer perikymata pattern and in numerous studies so-called focal holes have been seen [32] . Using scanning electromicroscopy, de Marsillac et al found that micro-sized diffusion pathways through intercrystalline and interprismatic spaces could be detected on the surface of carious enamel [33] . On the other hand, our previous investigation has revealed that CS-AMEL hydrogel works through the nano-sized amelogenin-Ca-P clusters that eventually evolve into enamel-like co-aligned crystals [9] .…”
Section: Discussionmentioning
confidence: 99%
“…In initial carious lesions, the relatively intact surface layer generally exhibits a clearer perikymata pattern and in numerous studies so-called focal holes have been seen [32] . Using scanning electromicroscopy, de Marsillac et al found that micro-sized diffusion pathways through intercrystalline and interprismatic spaces could be detected on the surface of carious enamel [33] . On the other hand, our previous investigation has revealed that CS-AMEL hydrogel works through the nano-sized amelogenin-Ca-P clusters that eventually evolve into enamel-like co-aligned crystals [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the surface of the initial carious lesions remaining relatively intact, nano-sized AMEL-CaP clusters can permeate the deep layer through micro-sized diffusion pathways in the inter-crystalline and inter-prismatic space [ 42 , 43 ]. In situ biomineralisation induced by chitosan (CS)-AMEL was found to result in the formation of a dense interface between the newly grown layer and natural enamel, such that the mechanical properties of the enamel-like layer improved compared to those of etched enamel (Table 1 ) [ 44 ].…”
Section: Biomimetic Systems For Enamel Restorationmentioning
confidence: 99%
“…A detailed understanding and quantification of the involved processes will allow for deriving alternative tooth repair procedures. The caries lesions can be investigated ex vivo taking advantage of a wide variety of methods including microradiography [ 2 ], light microscopy [ 3 ], electron microscopy [ 3 , 4 ], confocal laser scanning microscopy [ 5 ], atomic force microscopy [ 6 ], and nano-indentation [ 7 ]. Some of these techniques require destructive tissue preparation or just yield a two-dimensional snapshot of the three-dimensional lesion at a particular stage during disease development.…”
Section: Introductionmentioning
confidence: 99%